Spawning, Larviculture, and Salinity Tolerance of Alewives and Blueback Herring in Captivity. (8th June 2015) - DiMaggio, Matthew A.; Pine, Harvey J.; Kenter, Linas W.; Berlinsky, David L.
Abstract: Precipitous declines in wild populations of river herring species (Alewives Alosa pseudoharengus and Blueback Herring A. aestivalis ) have led to increased interest in stock enhancement efforts. Additionally, their popularity as a baitfish among recreational anglers has generated interest in commercial production of these species for marine baitfish markets. The objective of this investigation was to elucidate practical culture protocols for captive propagation of these species for commercial and restoration purposes. Wild Blueback Herring, captured during their annual spawning migration, spawned in tanks volitionally, while Alewives required exogenous hormone administration. Larvae of both species were successfully raised through metamorphosis using a feeding regime comprised of enriched rotifers followed by Artemia nauplii and a commercially available diet. Survival of early larvae acclimated to salinities ranging from 5‰ to 15‰ was high for both species (>94.0%) while that for older larvae acclimated to 15, 20, and 30‰ ranged from 64.7% to 95.3%. Juveniles raised at varying salinities (0–30‰) exhibited high survival (95.6–100.0%) and excellent feed conversion ratios (≤1.31) in all treatments. In acute salinity transfer experiments, high survival was observed when fish of both species (233–275 d posthatch) were transferred from low to high salinities, but low survival (10.0% and 3.3%) was observed in Alewives transferred from 15‰ or 30‰ to freshwater (0‰). A nodular fibrotic growth was found on 3.7% and 10.1% of the cultured Alewives and Blueback Herring (≥231 d posthatch), respectively, that likely followed tissue trauma and ulceration. The results of these studies provide a framework for river herring culture in recirculating systems.